Pengembangan Desain Antarmuka Sistem Informasi Keuangan Kas RT Berbasis Mobile dengan Metode Design Thinking - Wibowo, Ari Putra Wibowo; Arief Soma Dharmawan; Muhammad Faizal Kurniawan; Devi Sugianti; Risqiati (LogicLink, 2024)
This research aims to develop a mobile-based financial information system design for RT Cash, using the design thinking method. The object of this research is RT 06, Kelurahan Kuripan Yosoreko, Kecamatan Pekalongan Selatan, Kota Pekalongan. RT 06 is one of the RTs that has utilized information technology for recording and reporting residents' cash. Currently, the information system used in RT 06, Yosorejo Village is a web-based information system with several user accounts for RT officials, including the RT Chairman, Treasurer, and Secretary. The design thinking method is used because it can be used to explore various possibilities that prioritize the user as the main actor. The stages performed in this research include empathize, define, ideate, prototype, and testing. The research results indicate that the development of this mobile-based financial information system design for RT Cash is acceptable and can be used as a solution for users. Based on the usability testing conducted, all selected respondents were able to complete all test scenarios on the new interface design